Validation of the Chinese version of the Pregnancy-related Anxiety Questionnaire-Revised (PRAQ-R) and its distinction from general anxiety and depression in pregnant women. (2nd July 2020) - Chan, Chui Yi; Lee, Antoinette Marie; Koh, Yee Woen; Tang, Catherine So Kum
Abstract: Objective: This study aims to evaluate the reliability and validity of the translated Chinese-Cantonese version of the Pregnancy-Related Anxiety Questionnaire-Revised (PRAQ-R) in a sample of pregnant women in Hong Kong, China. It also aims to determine whether pregnancy-related anxiety changes significantly across trimesters and if it is differentiated from general anxiety and depression. Method: This study adopts a prospective longitudinal design with a quantitative approach. A consecutive sample of 186 Chinese pregnant women from hospitals in Hong Kong are assessed using the translated Chinese-Cantonese version of the PRAQ-R and other standardized instruments at three time points during the first to third trimester. Results: A confirmatory factor analysis revealed a three-factor structure of the Chinese-Cantonese version of the PRAQ-R, including fear of giving birth, fear of bearing a physically or mentally handicapped child, and concern about one's appearance. The internal consistency was excellent ( α  = 0.88 to 0.91) for all of the items in the PRAQ-R across the three trimesters. The average variance extract (AVE) and composite reliability (CR) for each factor were greater than the recommended level of CR > 0.70 and AVE > 0.50. Multiple regression analyses showed that a combination of general anxiety and depression explained a small proportion of the variance (10–29%) in the PRAQ-R subscales during the three trimesters. Conclusions: The Chinese-Cantonese version of the PRAQ-R has good validity and reliability, and the results provide evidence of its relevance for Chinese pregnant women with pregnancy-related anxiety in Hong Kong. The finding also shows that pregnancy-related anxiety is a relatively distinctive form of anxiety that is different from general anxiety and depression.